MENJAGA VOLATILITAS NILAI TUKAR: FAKTOR PENDUKUNG PENGEMBANGAN BISNIS DI ASEAN - Rahutami, A. Ika (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2008)
Currently, economic globalization brings a big impact for business environment in Indonesia. The competition capability is one of requirement to access a broader market. Instead of the manufacture’s competence itself, a conducive macroeconomic condition will support the global competition. If the target of business is a wider market, the stability of currency should be a sustain factor. One of the currency’s risks is exchange rate volatility. The bigger volatility, the bigger risk and unstable condition hence will impede intervention to foreign market. Nowadays ASEAN establish the new integration process after the AFTA trading agreement is not sufficient to construct market and generate a better welfare. AFTA is created for a better and extensive economic integration in 2020 namely ASEAN Economic Community (AEC). Based on more stable economic integration, European Union, it can be concluded that a monetary agreement, moreover the common currency wi l l create more stable economic condition and exchange rate. A heterogeneous economic system, per capita income, economic level, currency and exchange rate among ASEAN countries being a problem for adjustment. This study observes the exchange rate volatility in ASEAN countries. The results of this study showed that the based on the financial integration framework indicator, ASEAN countries require a lot of adjustment that will make a more convergence economic policy to construct financial integration frameworkKeywords : Globalization, AEC, currency volaality, bussines development